2013
DOI: 10.1094/cchem-01-13-0008-fi
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bran Addition on Water Properties and Gluten Secondary Structure in Wheat Flour Doughs Studied by Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy

Abstract: The aim of this work was to elucidate the underlying physical mechanism(s) by which bran influences whole grain dough properties by monitoring the state of water and gluten secondary structure in wheat flour and bran doughs containing 35–50% moisture and 0–10% added bran. The system was studied with attenuated total reflectance (ATR) FTIR spectroscopy. Comparison of the OH stretch band of water in flour dough with that in H2O‐D2O mixtures having the same water content revealed the formation of two distinct wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 26 publications
4
51
1
Order By: Relevance
“…Vector‐normalized H 2 O–D 2 O reference spectra of the same water content were digitally subtracted along with a vector‐normalized bran spectrum when appropriate. The difference spectra were subsequently analyzed in the 3,000–3,800 cm −1 region to detect shifts in the state and/or structure of water due to processing and bran addition (Bock et al, ; Bock & Damodaran, ; Jain, Varshney, & Maitra, ; Sutander, Ahn, & Franses, ; Zelent & Vanderkooi, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vector‐normalized H 2 O–D 2 O reference spectra of the same water content were digitally subtracted along with a vector‐normalized bran spectrum when appropriate. The difference spectra were subsequently analyzed in the 3,000–3,800 cm −1 region to detect shifts in the state and/or structure of water due to processing and bran addition (Bock et al, ; Bock & Damodaran, ; Jain, Varshney, & Maitra, ; Sutander, Ahn, & Franses, ; Zelent & Vanderkooi, ).…”
Section: Methodsmentioning
confidence: 99%
“…While most existing studies have focused on the secondary structural features of refined systems, there have been a few studies that have evaluated secondary structure in whole grain systems. Bock and Damodaran () and Bock et al () found the presence of bran altered water state and structure in model gluten and bread dough systems, consequently leading to an increase in β‐sheet structures at the expense of β‐turns and/or aperiodic structures. This was hypothesized to be partially responsible for the detrimental impact of bran in whole wheat bread.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also the competition for water between meal constituents might explain the detrimental effect of wheat bran on bread properties. More recently, Bock, Connelly, and Damodaran (2013) observed a redistribution of water among dough components when wheat bran is added, resulting into partial dehydration and structural changes of the gluten proteins. A third possible explanation of the impact of bran on bread properties is its steric hindrance during dough development, disturbing the formation of an optimal gluten network (Gan, Ellis, Vaughan, & Galliard, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover in combination with new methods of sample presentation such as Attenuated Total Reflectance (ATR) e which enables analysis of food matrix directly in the solid or liquid state without further preparation e FTIR allows the acquisition of high-quality spectra with high reproducibility from previously quite intractable materials ( Van de Voort, Sedman, Emo, & Ismail, 1992;Wilson, Goodfellow, & Belton, 1988). ATR-FTIR spectroscopy has been used to probe gluten secondary structure in dough under various conditions and formulations Bock, Connelly, & Damodaran, 2013;Jazaeri et al, 2015;Kaddour et al, 2008;Li, Dobraszczyk, Dias, & Gil, 2006;Meziani et al, 2011;Sivam et al, 2012;Wang et al, 2014;Wellner et al, 2005). More recently, the poor quality of bran-enriched bread was explained by the conversion of b-turn structure into b-sheet and random structures when bran is added to the gluten or to wheat .…”
Section: Introductionmentioning
confidence: 99%